Complex assessment of cardiovascular risk factors at Health Centres - M. V. Avdeeva (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess the potential of Health Centres in identification of individuals at higher cardiovascular risk. Material and methods. In total, 1583 individuals (mean age 51,79±14,75 years) participated in a complex screening programme, including laboratory and instrumental examination. Results. The screening resulted in identification of individuals with high normal blood pressure (HNBP) and newly diagnosed arterial hypertension (AH) (prevalence 21%). In participants with HNBP, a combination of 2 risk factors (RFs) was the most prevalent (37,79%), while in people with newly diagnosed AH, a combination of 3 RFs was the most common (39,88%). The prevalence of autonomic dysfunction or “Myocardium” parameter increase, as an isolated RF, reached 8,84% and 9,45%, respectively. Abnormal ankle-brachial index (ABI) values were registered in 29,66% of the participants. In 18,97%, ABI values exceeded 1,3, while in 10,69%, they were under 0,9. ABI screening identified 11% of asymptomatic individuals with increased cardiovascular risk. Conclusion. A screening programme could identify individuals with preAH, primary autonomic dysfunction, functional myocardial instability, or subclinical atherosclerosis of peripheral arteries. Therefore, all subjects with increased cardiovascular risk require lifestyle modification and additional laboratory and instrumental examination, in order to assess the target organ damage and the need for pathogenetic therapy.